2006
DOI: 10.1057/palgrave.ijea.2150015
|View full text |Cite
|
Sign up to set email alerts
|

Building Relationships of Brand Community in Higher Education: A Strategic Framework for University Advancement

Abstract: Loyal alumni are a mainstay of fi nancial support for many universities. This empirical study of university alumni situates the emerging theory of brand community within the world of university development and advancement. The study measures key relationships that one would expect to fi nd in a healthy university brand community. Most importantly, this research demonstrates the powerful contribution that understanding and managing brand community can make to those interested in the advancement of higher educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 23 publications
0
57
0
3
Order By: Relevance
“…Con ello, y en relación a la imagen de marca y el personal estudiante universitario, McAlexander et al (2006) consideran que la imagen de marca de una universidad se maximiza a través de la construcción de relaciones sostenibles en el tiempo entre los trabajadores de la propia institución y la comunidad estudiantil. Por su parte, Sung y Yang (2008) añaden que si una universidad consigue generar un modelo de marca basado en personalidad fuerte, prestigio externo y reputación, ello hará que esta mejore su imagen de marca con respecto a sus estudiantes.…”
Section: H2 Imagen De Marcaunclassified
“…Con ello, y en relación a la imagen de marca y el personal estudiante universitario, McAlexander et al (2006) consideran que la imagen de marca de una universidad se maximiza a través de la construcción de relaciones sostenibles en el tiempo entre los trabajadores de la propia institución y la comunidad estudiantil. Por su parte, Sung y Yang (2008) añaden que si una universidad consigue generar un modelo de marca basado en personalidad fuerte, prestigio externo y reputación, ello hará que esta mejore su imagen de marca con respecto a sus estudiantes.…”
Section: H2 Imagen De Marcaunclassified
“…Empirical research on brand communities in higher education is not limited to the verification of the above model. Other studies focused on relationship of the brand community integration with loyalty-related behaviors among students and alumni (such as future donations, purchase of university logo merchandise, positive recommendation) (McAlexander, Koenig, Schouten, 2006;McAlexander, Koenig, 2010;Martin, Moriuchi, Smith, Moeder, Nichols, 2015;Dziewanowska, 2016).…”
Section: Brand Communities In Higher Educationmentioning
confidence: 99%
“…McAlexander, Koenig and Schouten (2006) presented and tested a model reflecting various relationships existing within university brand communities. They also emphasized the importance of brand community integration and suggested that the biggest value results from looking at these relationships collectively, not separately.…”
Section: Brand Communities In Higher Educationmentioning
confidence: 99%
“…In addition, alumni relations programs must remember a college is a marketing institution that offers a range of services through its brand (McAlexander et al, 2006). Although education's product is elusive, the strength of a college's brand relationship with consumers is apparent in the frequency consumers adorn themselves and spaces with branded merchandise (McAlexander et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…University branding is used to give face to an institution and increase valued behaviors such as "donations, college referrals, engagement in alumni groups, and participation in continuing education" (McAlexander et al, 2006, p. 115). Understanding and managing a university or college's brand can have a strong impact on advancement programs (McAlexander et al, 2006). Consistent communication and relationship cultivation with alumni is often the backbone of the institution (CASE, 2014a;CASE, 2014b).…”
Section: Introductionmentioning
confidence: 99%